Sample transport validation: experience of a medium-sized laboratory - Vivianne A. Lopes; Juliana S. Silveira; Letícia B. S. Santos; Missilene da Conceição P. Nunes; Manuel S. Faria (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT INTRODUCTION: The adequacy of biological samples is a critical and important item in the clinical laboratory, so that reliable results can be obtained for patients. OBJECTIVE: To ensure integrity and stability of biological samples during the transport process. METHOD: Concurrent validation was carried out - in parallel with the production process and distribution of the product, from January to March 2017. The blood samples were packaged primarily in tube racks, and those of urine, feces and microbiological materials were packed in plastic bags. Materials were wrapped in a blanket of absorbent material to ensure temperature integrity and to avoid possible material losses. Thermal bags were the containers used to carry the samples. There were five transport routes, with two daily routes for each collection unit. A recommendation of the number of ice packs, predefined by the laboratory, was followed. RESULTS AND CONCLUSION: In the first month, the pre-established temperatures (blood: 10°C to 22°C/urine-feces: 2°C to 8°C) were not reached until arrival at the central laboratory, and the amount of ice in each bag was gradually increased, daily, until reaching the ideal temperature, in all collection units and the central. Transport routes were changed three times in the most distant units. Materials that arrived outside specifications were processed with restrictions, and results were evaluated by the professional responsible for the release. After these modifications, the temperature records of the biological materials were in accordance with the current legislation and the defined specifications, thus validating the process.